The role of phytochemicals in modulating the gut microbiota: Implications for health and disease - Amandeep Singh; Prabhjot Kaur; Manish Kumar; Sheeba Shafi; Prabhat Kumar Upadhyay; Abhishek Tiwari; Varsha Tiwari; Naresh Kumar Rangra; Vidhya Thirunavukkarasu; Sheeba Kumari; Debajyoti Roy; Maitrayee Ghosh; et al. (Medicine in Microecology)
The phytochemicals found in vegetables and fruits exert considerable impacts on the gut microbiota and human health. Polyphenols, flavonoids and terpenoids are some of these compounds that can increase the growth of good bacteria, while reducing the growth of the bad ones hence maintaining gut health. Phytochemicals positively modulate gut microbiota that in turn enhances gut barrier integrity, immune system and metabolism. They have also been associated with the disease prevention and control approaches that include inflammatory bowel disease, obesity, diabetes and heart ailments. These modifications are often affected by the particular composition of each individual's gut microbiota as well as variables like dose, bioavailability and mechanism of phytochemical such as its antioxidant capacity, anti-inflammatory effects, or ability to modulate metabolic pathways. Saponins, capsaicin and polyphenols (flavonoids, quercetin, and catechins) are promising phytochemicals for regulating the gut flora. These substances affect the chemical composition of microorganisms, decreasing dangerous pathogens and increasing helpful bacteria like Lactobacillus and Bifidobacterium. Additionally, they promote the synthesis of bioactive metabolites that have antibacterial and anti-inflammatory properties. Based on individual microbial profiles, this targeted strategy may enhance gut health, prevent ailments like diabetes and obesity, and maximize treatment results. This review aims to explore the possibility and potential of phytochemicals as therapeutic agents for disease prevention and personalized medicine to advance understanding of their biological effects in disease prevention and modulation. Such knowledge might offer novel microbiota-directed approaches to improving human well-being.